Safety and Efficacy of Low-Dose Tirofiban Combined With Intravenous Thrombolysis and Mechanical Thrombectomy in Acute Ischemic Stroke: A Matched-Control Analysis From a Nationwide Registry - Ma, Gaoting; Li, Shuo; Jia, Baixue; Mo, Dapeng; Ma, Ning; Gao, Feng; Huo, Xiaochuan; Luo, Gang; Wang, Anxin; Pan, Yuesong; Song, Ligang; Sun, Xuan; et al. (Frontiers in Neurology, 2021)
Purpose: Tirofiban administration to acute ischemic stroke patients undergoing mechanical thrombectomy with preceding intravenous thrombolysis remains controversial. The aim of the current study was to evaluate the safety and efficacy of low-dose tirofiban during mechanical thrombectomy in patients with preceding intravenous thrombolysis. Methods: Patients with acute ischemic stroke undergoing mechanical thrombectomy and preceding intravenous thrombolysis were derived from “ANGEL-ACT,” a multicenter, prospective registry study. The patients were dichotomized into tirofiban and non-tirofiban groups based on whether tirofiban was administered. Propensity score matching was used to minimize case bias. The primary safety endpoint was symptomatic intracerebral hemorrhage (sICH), defined as an intracerebral hemorrhage (ICH) associated with clinical deterioration as determined by the Heidelberg Bleeding Classification. All ICHs and hemorrhage types were recorded. Clinical outcomes included successful recanalization, dramatic clinical improvement, functional independence, and mortality at the 3-month follow-up timepoint. Successful recanalization was defined as a modified Thrombolysis in Cerebral Ischemia score of 2b or 3. Dramatic clinical improvement at 24 h was defined as a reduction in NIH stroke score of ≥10 points compared with admission, or a score ≤1. Functional independence was defined as a Modified Rankin Scale (mRS) score of 0–2 at 3-months. Results: The study included 201 patients, 81 in the tirofiban group and 120 in the non-tirofiban group, and each group included 68 patients after propensity score matching. Of the 201 patients, 52 (25.9%) suffered ICH, 15 (7.5%) suffered sICH, and 18 (9.0%) died within 3-months. The median mRS was 3 (0–4), 99 (49.3%) achieved functional independence. There were no statistically significant differences in safety outcomes, efficacy outcomes on successful recanalization, dramatic clinical improvement, or 3-month mRS between the tirofiban and non-tirofiban groups (all p > 0.05). Similar results were obtained after propensity score matching. Conclusion: In acute ischemic stroke patients who underwent mechanical thrombectomy and preceding intravenous thrombolysis, low-dose tirofiban was not associated with increased risk of sICH or ICH. Further randomized clinical trials are needed to confirm the effects of tirofiban in patients undergoing bridging therapy.